An equation demonstrates the equality of two expressions. x2+12x+13 is only one expression.
For example,
x+y : expression, not equation
x+5 = 3 : equation
3 - x = 12x - 1 Add x to both sides of the equation: 3 = 13x - 1 Add 1 to both sides of the equation: 4 = 13x Divide both sides of the equation by 13: 4/13 = X
5
To solve the equation 1 + 2x + 13 = 9, you first need to simplify by combining like terms. Subtract 1 and 13 from both sides of the equation to isolate the variable term. This gives you 2x = -5. Finally, divide by 2 on both sides to solve for x, which gives you x = -5/2 or -2.5.
Set up the equation and solve: x + 5 = -13 (next subtract 5 from each side of the equation to solve for x) x = -18
Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s
3 - x = 12x - 1 Add x to both sides of the equation: 3 = 13x - 1 Add 1 to both sides of the equation: 4 = 13x Divide both sides of the equation by 13: 4/13 = X
17
5
To solve the equation 1 + 2x + 13 = 9, you first need to simplify by combining like terms. Subtract 1 and 13 from both sides of the equation to isolate the variable term. This gives you 2x = -5. Finally, divide by 2 on both sides to solve for x, which gives you x = -5/2 or -2.5.
If: 2a+13 = 5a+1 Then: a = 4
Set up the equation and solve: x + 5 = -13 (next subtract 5 from each side of the equation to solve for x) x = -18
13 = 12x - 2y Adding 2y to both sides: 13 + 2y = 12x Subtracting 13 from both sides: 2y = 12x - 13 Divide both sides by 2: y = 6x - 6.5
Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s
3 -x = 12x -1 add x to both sides 3 = 13x -1 add 1 to both sides 4 = 13X divide both sides by 13 4/13 = x
Without an equality sign the given expression is not an equation but it can be simplified to: W-15
3h+13 = 7 3h = 7-13 3h = -6 h = -2
x2+12x-13=0 The factor of x2+12x-13 is: (x+13)(x-1) So: x+13 = 0 or x-1 = 0 The answer is: x=-13 or x=1